Expression of C5a and its receptor in canine spontaneous tumours: a preliminary finding - Ganti, Norhaifa; Bachek, Noor Farhana; Kamarudin, Nurul Hazwani; Kosni, Nurneqman Nashreq; Md. Ajat, Mohd Mokrish; Ahmad, Hafandi; Selvarajah, Gayathri Thevi; Mohd Noor, Mohd Hezmee (Universiti Putra Malaysia Press, 2016)
A study of the development of spontaneous tumours in dogs gives many benefits in oncology research due to the similarity between dog and human cancer in terms of epidemiologic, biologic and clinical features. There is evidence that the complement component 5 anaphylatoxin (C5a) and its receptor are involved in the development of many types of tumour due to its inflammatory properties. The purpose of this study was to determine the expression of C5a on several types of canine spontaneous tumour i.e. mammary tumour, lung tumour, testicular tumour and melanoma. The expression of C5a in these tumours was compared with normal tissue from the breasts, lungs, testes and skin. The total of eight post-mortem canine tissues were collected from University Veterinary Hospital (UVH), University Putra Malaysia and stored in a preservative solution (RNAlater) to keep the RNA from degrading. The RNA was extracted using the Qiagen RNA Extraction Kit and a cDNA synthesis was carried out using a one-step PCR kit (Promega, USA). The expression of C5a was determined using reverse transcriptase PCR (RT-PCR) and Quantitative real-time PCR (qPCR) techniques. The results showed that all types of tumour gave higher expression of C5a compared to normal tissue. This means that the CT value for the tumours was below 30 cycles except for melanoma and the expression of C5a of normal tissues was above 30 cycles. This finding suggests that C5a and its receptor may be involved in the development of tumours in dogs and can be used as a tumour biomarker for both animals and humans in the future. Nevertheless, further studies investigating the mechanisms of C5a and its receptor in canine spontaneous tumour are necessary.